Pendidikan Seks dalam Lontar Smara Krida Laksana - Ni Putu Oka Anggi Carissa Putri (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2021)
In the lontar contains a lot of education as contained in the Smara Krida Laksana lontar, the Smara Krida Laksana lontar contains knowledge about sexual intercourse etiquette, drugs, ingredients, and spells used as sexual treatment. Sex is not only known to married people but sex can also be known by teenagers as knowledge when married. So that in modern times like today teenagers are not exposed to free sex. As explained above, the contents of this lontar can be said to be unique because it talks about the treatment of sexuality. So that the research is said to be valid, the method of collecting data is used. The type of data used is qualitative data because the data obtained is in the form of sentences, not numbers. The methods used to collect data are literature, documents, and interviews. In the data analysis, data reduction, data presentation, data conclusions were used. The results of this study were in the manners and sex treatment system, it was found that the manners of sexual intercourse were good for married people and the drugs, ingredients, and spells used as treatment. The second problem formulation discusses sex education, religious education and ethics education are obtained, and the last problem formulation deals with the behavior of teenagers' sexual relations today and the relationship between Smara Krida Laksana's lontar with married people, especially teenagers today.